2007
DOI: 10.4315/0362-028x-70.6.1366
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simultaneous Quantitation of Escherichia coli O157:H7, Salmonella, and Shigella in Ground Beef by Multiplex Real-Time PCR and Immunomagnetic Separation

Abstract: The objective of this study was to establish a multiplex real-time PCR for the simultaneous quantitation of Escherichia coli O157:H7, Salmonella, and Shigella. Genomic DNA for the real-time PCR was extracted by the boiling method. Three sets of primers and corresponding TaqMan probes were designed to target these three pathogenic bacteria. Multiplex real-time PCR was performed with TaqMan Universal PCR Master Mix in an ABI Prism 7700 Sequence Detection System. Final standard curves were calculated for each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 30 publications
3
81
0
Order By: Relevance
“…These methods are frequently being replaced with more-rapid and -sensitive molecular biology-based techniques. RT-PCR is a recent advance in molecular detection that has been used successfully for the rapid identification of a wide array of bacterial pathogens in specific food matrices (12,15,22,34,36,40). However, various food products have been shown to interfere with PCR assays, resulting in potentially false-negative results (1,22,31,32,33,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are frequently being replaced with more-rapid and -sensitive molecular biology-based techniques. RT-PCR is a recent advance in molecular detection that has been used successfully for the rapid identification of a wide array of bacterial pathogens in specific food matrices (12,15,22,34,36,40). However, various food products have been shown to interfere with PCR assays, resulting in potentially false-negative results (1,22,31,32,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods require lengthy enrichment steps prior to the application of the respective methods. Real-time PCR (RT-PCR) is a promising new method currently used for detection of a wide variety of bacterial pathogens in food matrices (12,15,22,34,40). However, this technique can be ineffective for the detection of Salmonella serotype Enteritidis in foods such as eggs due to the presence of PCR-inhibitory components (41).…”
mentioning
confidence: 99%
“…Some new methods have been developed, including immunoassays (Magliulo et al, 2007), immunomagnetic separations (Wang et al, 2007), nucleic acid probe-based methods based on hybridization and polymerase chain reaction (PCR) (Johnston et al, 2005), and the DNA microarrays (Jin et al, 2005). However, many of these methods are so time-consuming, expensive or complicated that they are not suitable for fast detection of E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that only one food item was positive for Salmonella [57]. Wang et al reported a qPCR method to detect Salmonella in raw sausage meat with detection limit of 4 cfu/g [58]. He also used this method to quantify Salmonella detection limits of 2.5 cfu/25 g for salmon and minced meat, 5 cfu/25 g of chicken meat, and 5 cfu/25 ml for raw milk, respectively [59].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%